Ecological regime shift drives declining growth rates of sea turtles throughout the West Atlantic. (1st June 2017) - Bjorndal, Karen A.; Bolten, Alan B.; Chaloupka, Milani; Saba, Vincent S.; Bellini, Cláudio; Marcovaldi, Maria A. G.; Santos, Armando J. B.; Bortolon, Luis Felipe Wurdig; Meylan, Anne B.; Meylan, Peter A.; Gray, Jennifer; Hardy, Robert; et al.
Abstract: Somatic growth is an integrated, individual‐based response to environmental conditions, especially in ectotherms. Growth dynamics of large, mobile animals are particularly useful as bio‐indicators of environmental change at regional scales. We assembled growth rate data from throughout the West Atlantic for green turtles, Chelonia mydas, which are long‐lived, highly migratory, primarily herbivorous mega‐consumers that may migrate over hundreds to thousands of kilometers. Our dataset, the largest ever compiled for sea turtles, has 9690 growth increments from 30 sites from Bermuda to Uruguay from 1973 to 2015. Using generalized additive mixed models, we evaluated covariates that could affect growth rates; body size, diet, and year have significant effects on growth. Growth increases in early years until 1999, then declines by 26% to 2015. The temporal (year) effect is of particular interest because two carnivorous species of sea turtles—hawksbills, Eretmochelys imbricata, and loggerheads, Caretta caretta —exhibited similar significant declines in growth rates starting in 1997 in the West Atlantic, based on previous studies. These synchronous declines in productivity among three sea turtle species across a trophic spectrum provide strong evidence that an ecological regime shift (ERS) in the Atlantic is driving growth dynamics. The ERS resulted from a synergy of the 1997/1998 El Niño Southern Oscillation (ENSO)—the strongest on record—combined with an unprecedented warming rate over the last two to three decades. Further support is provided by the strong correlations between annualized mean growth rates of green turtles and both sea surface temperatures (SST) in the West Atlantic for years of declining growth rates ( r  = −.94) and the Multivariate ENSO Index (MEI) for all years ( r  = .74). Granger‐causality analysis also supports the latter finding. We discuss multiple stressors that could reinforce and prolong the effect of the ERS. This study demonstrates the importance of region‐wide collaborations. Abstract : Somatic growth is an integrated, individual‐based response to environmental conditions, especially in ectotherms. The authors compiled extensive growth data for green sea turtles throughout the West Atlantic from 30 sites from Bermuda to Uruguay from 1973 to 2015. Growth rates declined significantly from 1999 to the present. Synchronous declines in growth rates among three sea turtle species across a trophic spectrum provide strong evidence that the ecological regime shift (ERS) that occurred in the late 1990s in the Atlantic is driving growth dynamics. The ERS combined with an unprecedented warming rate over the last two to three decades and cumulative impacts of ongoing anthropogenic degradation of foraging habitats in the region slowed growth in these mega‐consumers. The summary conclusion that productivity of sea turtles is lower at warmer temperatures is not good news in an age of warming seas.